Perspective of Cikahuripan Villagers on Traditional Health Service Provisions in Government Regulation No. 103 Year 2014 - Hashfi Khairuddin; M. Rizal Chaidir; Deni K. Sunjaya (Althea Medical Journal, 2020)
Background: Traditional health service is one of the health services that is still currently used in Indonesia, especially in rural communities. The government has been regulating these services since 2014. Despite its long existence, there is a recent increase of potential regulation violation among traditional health service providers. This study aimed to explore the perspective of the Cikahuripan Villagers on Government Regulation on traditional health services.Methods: This was a qualitative study using in-depth interviews and direct observations on traditional health services in Cikahuripan Village. Sixteen informants consisting of 8 villagers who met the inclusion criteria and another 8 informants in the triangulation negative case analysis, member checking, peer debriefing, and observation was involved.Results: There were two different perspectives in the community on traditional health service provisions in the Government Regulation. Supporters of the regulation believed that the regulation would make traditional health services more responsive and safer, which would improve service quality and health benefits as well as imposing effective sanctions. In contrast, the opposition believed that regulations were too late, would make the costs for licensing expensive, and too complicated.Conclusion: There are two different public perspectives on the regulation of traditional health services, which are supporting and opposing the regulation. It is expected that the local government create a derivative of the regulation by making adjustment to the community’s situation.